2006
DOI: 10.1213/01.ane.0000220947.02689.9f
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Flow Index Is a Reliable and Early Indicator of Regional Block Success

Abstract: We investigated the usefulness of peripheral flow index (PFI) measurement using a standard pulse oximetry digit probe for early prediction of successful regional blocks. Sixty-six patients scheduled for limb surgery underwent either axillary or sciatic block using a nerve stimulator technique with mepivacaine 1.5%. PFI, which is the ratio of the pulsatile versus the nonpulsatile component of the pulse oximetry signal, was recorded from 10 min before block insertion until 30 min afterwards. PFI recordings of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 7 publications
4
77
3
2
Order By: Relevance
“…The laser Doppler peripheral flow index (PFI) is a reliable parameter to predict successful regional anesthesia after axillary or sciatic blocks. 4 An increase in PFI went along with an increase in local blood flow and local vasodilatation. The present data show that PI (like PFI) is a sensitive parameter to indicate loss of vasomotor tone induced by local anesthetics.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The laser Doppler peripheral flow index (PFI) is a reliable parameter to predict successful regional anesthesia after axillary or sciatic blocks. 4 An increase in PFI went along with an increase in local blood flow and local vasodilatation. The present data show that PI (like PFI) is a sensitive parameter to indicate loss of vasomotor tone induced by local anesthetics.…”
Section: Discussionmentioning
confidence: 98%
“…3 The perfusion index can accurately reflect functional sympathetic blockade after interscalene nerve block placement as regional anesthesia induces vasodilatation and increased blood flow. 4 The objective of the current study was to assess the influence of interscalene nerve blockade on the PI of the anesthetized arm in comparison with PI values of the contralateral arm, and evaluate its use as an indicator for successful block placement.…”
Section: Résumémentioning
confidence: 99%
“…This stimulation of the sympathetic system increased the ST in the three treatments in this study. Epidural local anaesthetics induce a local vasodilatation and increase local blood by sympathetic block 28 with a consequent increase in ST in the blockade regions. Also MG decreases baseline tension in vascular smooth muscle and attenuates the vasoconstrictor response to vasopressor agents 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the perfusion index displays quite large individual variations, while their results had a large standard deviation. The peripheral flow index, the ratio of the pulsatile to non-pulsatile component of the pulse oximetry plethysmograph and an accurate indication of changes in digital blood flow [11], increased significantly due to the axillary block [12]. Cross et al [13] reported that the supraclavicular block increased blood flow in the fingers on the blocked hand, as well as cardiac output and blood flow of the non-blocked arm, while the increases in the non-blocked arm returned during the postoperative period.…”
Section: Discussionmentioning
confidence: 99%